Unifying and harmonizing substantive law and the role of conflict of laws - Boele-Woelki, Katharina (Pocketbooks of the Hague Academy of International Law., 2010)
Traditionally, conflict of law rules designate only national substantive law as the applicable law. Many unifying and harmonizing substantive law instruments of both States and non-State organizations, however, are designed specifically for application to cross-border relationships. Achieving this objective is, generally, hindered by conflict of law rules. The requirements which non-national law needs to fulfil in order to be accepted as the law governing a cross-border relationship deserve clarification. Not only uniform law, such as the CISG and the envisaged European substantive law instrum.